In mould laser welding for high precision polymer based optical components - Oliveira, N. (2013)
Assembling a complete subsystem as a rear lamp, it is necessary several different machines and tasks, for producing the final product. The technology presented in this paper has de capability to reduce the number of tasks needed for producing a final subsystem/product. In this case will be necessary only one injection moulding machine with three injection units. This was achieved by combining several technologies, as in-mould assembling, laser welding and LEDs. The challenges began by studying several polymeric materials, for understanding their behavior when they are welded by a laser beam. This was helpful also for determine the best welding properties. At the same time were analyzed different conductive polymers. This had the objective to determine their suitability for conducting the electric current between the different LEDs. The development of the rear lamp was made take in consideration the legislation of UNECE Vehicle Regulations - 1958 Agreement; Regulation No. 50 -Rev.2 - Position lamps, stop lamps, direction indicators for motorcycles. The results obtained present good input for producing in the same machine a complete and functional rear lamp.